2016
DOI: 10.5114/wiitm.2015.56999
|View full text |Cite
|
Sign up to set email alerts
|

C-reactive protein and procalcitonin predict anastomotic leaks following colorectal cancer resections - a prospective study.

Abstract: IntroductionEarly safe discharge is paramount for the success of ERAS following colorectal cancer resections. Anastomotic leakage (AL) has high morbidity, particularly if the patient has been discharged to the community.AimTo evaluate whether C-reactive protein (CRP) and procalcitonin (PCT) can predict AL before early discharge.Material and methodsFifty-five consecutive patients undergoing open and robotic colorectal cancer resections were included. C-reactive protein and PCT were measured pre-operatively, 8 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(66 citation statements)
references
References 20 publications
5
55
0
6
Order By: Relevance
“…Findings similar to ours, concerning the pro-inflammatory biomarker CRP have been reported by Zawadski et al (32) but with slightly higher discriminatory values for AL in their study by the 3rd postoperative day. An almost identical level of CRP and its postoperative timing and sensitivity for the diagnosis of AL was recently reported by Scepanovic et al (33).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Findings similar to ours, concerning the pro-inflammatory biomarker CRP have been reported by Zawadski et al (32) but with slightly higher discriminatory values for AL in their study by the 3rd postoperative day. An almost identical level of CRP and its postoperative timing and sensitivity for the diagnosis of AL was recently reported by Scepanovic et al (33).…”
Section: Discussionsupporting
confidence: 91%
“…Early elevation of measurable PCT (on the first or second postoperative days, for example), will be non-specific and reflect bacterial contamination or translocation secondary to bowel preparation. The PREDICS study (14) noted higher PCT levels on the 5th postoperative day than were found in our study on the 6th postoperative day, with Zawadski et al (32) also showing higher early PCT levels in their AL cases than noted in our study. Some authors have found that PCT adds no diagnostic value for an AL (14,35) whereas others have suggested that it is a better AL predictor when compared with CRP (36).…”
Section: Discussionsupporting
confidence: 53%
“…Another study by Marek showed that PCT measurement on POD 3 following colorectal cancer resection can positively identify patients at low risk of anastomotic leakage. The cut-off for PCT on POD 3 was 3.83 ng/ml, with sensitivity of 75% and specificity of 100% for AL [12]. A study performed in Spain also concluded that PCT is reliable predictor of major anastomotic leak after colorectal resection.…”
Section: Procalcitoninmentioning
confidence: 95%
“…The cut-off value of 140 mg/L on POD3 maximized the sensitivity (78%) and specificity (86%) of serum CRP in assessing the risk of leakage [6]. Serum CRP has been evaluated in other 11 studies [7][8][9][10][11][12][13][14][15][16][17]. In general, the CRP level was raised significantly days before the diagnosis of AL.…”
Section: C-reactive Proteinmentioning
confidence: 99%
See 1 more Smart Citation